2020
DOI: 10.29103/ijevs.v2i3.2429
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Use Interactive Learning Media Environment-based and Learning Motivation on Science Learning Outcomes

Abstract: The study aims to determine the effect of the use of interactive learning media environment-based and learning motivation on science learning outcomes. This research was conducted on grade V students of SDN Wijaya Kusuma 07 Jakarta Barat from September to November 2019. The method used was an experiment with a research design using two-way ANAVA (treatment by level 2x2), with the sample of 61 students was obtained using a multi-stage random sampling. Based on data analysis, it was obtained: First, the science … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 0 publications
2
8
0
4
Order By: Relevance
“…This research concluded that interactive learning media has effectiveness towards improving the competence of learners as seen from the learning results between pre-test and post-test scores. Sahronih et al (2020) also stated that the science learning outcomes of students who learn to use interactive learning media environment-based are higher than the science learning outcomes of students who learn to use non-interactive learning media. A similar study about interactive media was also done by Bustanil et al (2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This research concluded that interactive learning media has effectiveness towards improving the competence of learners as seen from the learning results between pre-test and post-test scores. Sahronih et al (2020) also stated that the science learning outcomes of students who learn to use interactive learning media environment-based are higher than the science learning outcomes of students who learn to use non-interactive learning media. A similar study about interactive media was also done by Bustanil et al (2019).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, research conducted by Prastika (2015) also showed that the application of interactive multimedia was effective in increasing student achievement. (Sahronih, S;Purwanto, A;Sumantri, M.S, 2020) in their research stated that the science learning outcomes of students who learn to use interactive learning media environment-based are higher than the science learning outcomes of students who learn to use non-interactive learning media.…”
Section: Introductionmentioning
confidence: 99%
“…Pembelajaran luring tersebut sepertinya mampu membangkitkan motivasi mereka, dan mengurangi sampai menghilangkan rasa bosan terhadap pembelajaran daring (Indrawati, 2020), dan direspon negatif oleh mahasiswa (Hidayati & Saputra, 2020;Mirawati et al, 2020). Adapun motivasi diketahui berdampak positif terhadap kemampuan belajar sains termasuk pada pembelajaran IAD (Permana, 2016;Sahronih et al, 2020;Astari et al, 2021). Sebagian besar mahasiswa membutuhkan waktu yang lebih panjang untuk melakukan habituasi.…”
Section: Hasil Dan Pembahasanunclassified
“…According to (Sahronih et al, 2020) one of the learning media that can be used by students in the era of technology society 5.0 is technology-based media such as interactive learning media, then Sahronih also explains that interactive learning media is a combination of images, animations, videos and sounds in software that must directly or indirectly allow users to interact. Learning must involve interaction between students, teachers, and learning materials with the use of interactive learning media will allow students to learn and understand the material again, students not only focus on learning media but they are required to interact with each other in the learning process (Rahayu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%